Optoelectronics: High‐Performance Photovoltaic Detector Based on MoTe2/MoS2 Van der Waals Heterostructure (Small 9/2018). Issue 9 (1st March 2018) - Chen, Yan; Wang, Xudong; Wu, Guangjian; Wang, Zhen; Fang, Hehai; Lin, Tie; Sun, Shuo; Shen, Hong; Hu, Weida; Wang, Jianlu; Sun, Jinglan; Meng, Xiangjian; et al.
Abstract : In article number1703293, Tie Lin, Weida Hu, Jianlu Wang, and co‐workers present a high performance photovoltaic photodetector based on MoTe2 /MoS2 Van der Waals heterojunction. The light‐induced charge transport under different biases is discussed. As self‐powered photodetectors, the vertical 2D p‐n junctions achieve a sensitive response and broad detection wavelength range. These properties indicate that 2D van der Waals junctions are promising for application in photo‐sensing, on‐chip logic circuits and so on.